Assessment of Paramedic Performance on Difficult Airway Simulation. (3rd May 2020) - Panchal, Ashish R.; Finnegan, Geoffrey; Way, David P.; Terndrup, Thomas
Abstract : Objective: Airway management is a common, important intervention for critically ill patients in the United States. A key element of prehospital airway management is endotracheal intubation (ETI). Prehospital ETI success rates have been shown to be as low as 77% compared to in-hospital rates of 95%. Given these rates, the use of backup airway devices is a necessary precaution for patient safety. The extent to which paramedics integrate backup airway use into their airway algorithm is unknown. The purpose of this study was to assess paramedic comprehensive airway management practices during a difficult airway simulation through which paramedics were obligated to consider alternatives to ETI. Methods: This was an observational study of airway management skills in active paramedics ( N = 198). A difficult airway simulation was conducted in a mobile simulation laboratory; a Type 3 ambulance with four video cameras including an endotracheal view to capture airway management. Recordings of paramedic performance were assessed using a 110-item checklist covering four key areas: 1) placement of an endotracheal tube; 2) application of backup airway following failed ETI; 3) ventilation of the patient; and 4) achievement of airway safety and quality measures. Results: Paramedics were highly trained with 12 years (IQR: 4–20) of advanced life support experience and a median of 40 prehospital intubations over their careers (IQR: 15–100). In this difficult airway setting, first pass ETI success rate was 55.6%. However, paramedics were challenged with airway management following a failed ETI. Only 9% of providers were prepared with a clear backup plan. Sixty-three percent of the paramedics successfully placed a backup airway within 3 attempts. During the simulation, only 14% properly ventilated at a rate of 10–12 breaths/min. Ventilations were maintained without interruptions (>30 sec) in 22% of simulations. Conclusion: In a difficult airway management scenario designed for low ETI success rates, even experienced paramedics were challenged with comprehensive airway management. This was exemplified by difficulties with the use of backup airway devices. Future work needs to be directed at identifying the key determinants for airway management success and the development of interventions to improve success with the use of a comprehensive airway management plan.